Where does the responsibility lie? : voluntary carbon offsetting in the aviation industry – the consumers’ perspective - Silfvenius, Pilvi (2024)
Climate change poses a serious threat to societies as well as the natural environment. Currently there are suggestions to keep global warming below 1.5 degrees Celsius in order to avoid irreversible damage. Commercial aviation is an industry where differ-ent climate change mitigation tools are being suggested, and one of these tools is voluntary carbon offsetting (VCO). This thesis looks further into consumer behaviour and their perceptions regarding voluntary offsetting within the aviation industry. There are different VCO projects that consumers can choose to invest in these mainly focus-ing on reforestation, renewable energy projects and sustainable aviation fuel. By con-ducting a quantitative survey as well as looking into existing literature this research looks into whose responsibility do consumers see offsetting as, what the feasibility of voluntary offsetting is as a climate change mitigation tool as well as potential alternatives solutions to voluntary offsetting. The findings show that consumers are hesitant about offsetting their flight emissions either due to the lack of knowledge or due to their distrust towards voluntary offsetting. Participants did not see that they alone would be responsible for offsetting their emissions from flying and very few had off-set their flights before, which could increase the importance of other mitigation efforts. However, should voluntary offsetting succeed as an emission reduction tool, there are indications that there is a need for regulations, transparency and overall, an increase of information around voluntary offsetting. Consumers as well as researchers have concerns regarding whether voluntary offsetting projects deliver on their promises, thus also indicating a need for more research on the long-term environmental impacts of voluntary offsetting projects.